Molecular characterization and sensitivity to demethylation inhibitor fungicides of Aspergillus fumigatus from orange-based compost. - Massimo Pugliese; Slavica Matić; Sanila Prethi; Ulrich Gisi; Maria Lodovica Gullino (PLoS ONE, 2018)
Aspergillus fumigatus, the causal agent of human aspergilloses, is known to be non-pathogenic in plants. It is present as saprophyte in different types of organic matter and develops rapidly during the high-temperature phase of the composting process. Aspergilloses are treated with demethylation inhibitor (DMI) fungicides and resistant isolates have been recently reported. The present study aims to estimate the abundance, genetic diversity and DMI sensitivity of A. fumigatus during the composting process of orange fruits. Composting of orange fruits resulted in a 100-fold increase in A. fumigatus frequency already after 1 week, demonstrating that the degradation of orange fruits favoured the growth of A. fumigatus in compost. Most of A. fumigatus isolates belonged to mating type 2, including those initially isolated from the orange peel, whereas mating type 1 evolved towards the end of the composting process. None of the A. fumigatus isolates expressed simultaneously both mating types. The 52 investigated isolates exhibited moderate SSR polymorphisms by formation of one major (47 isolates) and one minor cluster (5 isolates). The latter included mating type 1 isolates from the last sampling and the DMI-resistant reference strains. Only few isolates showed cyp51A polymorphisms but were sensitive to DMIs as all the other isolates. None of the A. fumigatus isolates owned any of the mutations associated with DMI resistance. This study documents a high reproduction rate of A. fumigatus during the composting process of orange fruits, requesting specific safety precautions in compost handling. Furthermore, azole residue concentrations in orange-based compost were not sufficient to select A. fumigatus resistant genotypes.